2015
DOI: 10.4103/0019-5413.152492
|View full text |Cite
|
Sign up to set email alerts
|

Locking plate versus retrograde intramedullary nail fixation for tibiotalocalcaneal arthrodesis

Abstract: Background:Tibiotalocalcaneal arthrodesis (TTCA) surgery is indicated for the end-stage disease of the tibiotalar and subtalar joints. Although different fixation technique of TTCA has been proposed to achieve high fusion rate and low complication rate, there is still no consensus upon this point. The purpose of this study is to compare the clinical efficacy of retrograde intramedullary nail fixation (RINF) and locking plate fixation (LPF) for TTCA.Materials and Methods:Fifty four patients who underwent TTCA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 23 publications
1
20
2
Order By: Relevance
“…Our bone union rate of 100% is consistent with outcomes reported in a recent systematic review by Van de Heuvel et al (99%) [ 17 ]. The bone union time also does not differ greatly from the literature: 14 weeks on average in our study and other recent studies [ 6 , 16 , 17 , 48 ], slightly shorter than the 18 reported by Zhang et al [ 4 ].…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Our bone union rate of 100% is consistent with outcomes reported in a recent systematic review by Van de Heuvel et al (99%) [ 17 ]. The bone union time also does not differ greatly from the literature: 14 weeks on average in our study and other recent studies [ 6 , 16 , 17 , 48 ], slightly shorter than the 18 reported by Zhang et al [ 4 ].…”
Section: Discussioncontrasting
confidence: 50%
“…Currently, similar bone union rates in TT arthrodesis with different fixation devices are reported in the literature; although, some studies report better results with plate fixation than with screw fixation alone [ 21 ] or with a retrograde nail [ 4 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…may be indicated. 25 We do not have experience with this procedure, and it was not indicated in any of our patients as the fibula was used as a lateral stabilizing biological plate.…”
Section: Discussionmentioning
confidence: 97%